2019
DOI: 10.1021/acs.jpcc.9b04340
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Spectroscopic and Thermochemical Characterization of Lithium–Aluminum-Layered Double Hydroxide Chloride: Implications for Lithium Recovery

Abstract: Lithium−aluminum-layered double hydroxide chloride (LDH) has been recently demonstrated to be a promising sorbent material for selective lithium extraction and recovery from geothermal brine. In this research, LDH samples synthesized from two different starting materials (alumina and gibbsite) and with two post-drying conditions (ambient-dried and oven-dried) as well as and Fe-doped LDH are studied using neutron vibrational spectroscopy. The results reveal differences in the ordering of interlayer water molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
3
18
1
Order By: Relevance
“…The reported enthalpies are based on dissolution enthalpies measured in our previous work (ΔH dissol ) (Wu et al, 2019a;Wu et al, 2019b). Because the dissolution enthalpy of liquid water in 5 N HCl solution is small, it was neglected in our previous calculations.…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported enthalpies are based on dissolution enthalpies measured in our previous work (ΔH dissol ) (Wu et al, 2019a;Wu et al, 2019b). Because the dissolution enthalpy of liquid water in 5 N HCl solution is small, it was neglected in our previous calculations.…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
“…Keeping in view the compositional flexibility of the Al(OH) 3 based LDHs, [Li-Al] LDHs with variable Li/Al ratios can be envisaged. When the Li/Al ratio is > 0.5, a layer of composition [Li 1+x Al 2-x (OH) 6 ] (1-2x)+ can be formulated, where the layer charge is lower than that found in the Synthesis and characterization (including powder x-ray diffraction, inductively coupled plasma-optical emission spectroscopy, differential scanning calorimetry, and thermogravimetry measurements) of these LDHs were performed previously (Wu et al, 2019a;Wu et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, Al(OH) 3 prepared by lithium desorption needs a high concentration of LiCl to readsorb lithium. [8][9][10][11][12]39] Previous in-situ XRD analyses reported that Al-(OH) 3 partly adsorbed lithium in a 4 M LiCl solution for 4 hours [11] but rarely adsorbed lithium in 1 M LiCl solution. [39] Selective adsorption of lithium ions.…”
Section: Anion Effect Of Single Salts On Initial Lithium Absorptionmentioning
confidence: 99%
“…[LiAl 2 (OH) 6 ] + (X À ) • yH 2 O (LiAl 2 -LDH) is considered one of the best representative hosts for lithium recovery from aqueous resources, such as brine and seawater, due to its promising characteristics of high chemical stability against lithium adsorption/ desorption in the aqueous phase and octahedral voids capable of accommodating lithium ions. [1][2][3][4][5][6][7][8][9] Typically, LiMnO x , Li 2 TiO 3 , and LiAl 2 -LDH have been used as sorbents for extraction of lithium from aqueous resources, [10] and LiAl 2 -LDH is a potential candidate for large-scale applications. Separation of lithium ions through precipitation of LiAl 2 -LDH powder has been accomplished by addition of aluminum salt in brine and reaction of aluminum ions with lithium ions.…”
Section: Introductionmentioning
confidence: 99%